2021
DOI: 10.3389/fphys.2020.630910
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 Levels Delay Skeletal Muscle Repair by Increasing Fatty Acid Oxidation

Abstract: Muscle dysfunction often occurs in patients with chronic obstructive pulmonary diseases (COPD) and affects ventilatory and non-ventilatory skeletal muscles. We have previously reported that hypercapnia (elevated CO2 levels) causes muscle atrophy through the activation of the AMPKα2-FoxO3a-MuRF1 pathway. In the present study, we investigated the effect of normoxic hypercapnia on skeletal muscle regeneration. We found that mouse C2C12 myoblasts exposed to elevated CO2 levels had decreased fusion index compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…As with studies on hypoxia, the levels of hypercapnia studied often exceed that seen in COPD patients, except perhaps under extreme conditions associated with acute exacerbations and/or in very severe patients needing lung transplant. Nonetheless, previous studies have shown that a PaCO 2 level of approximately 75 mmHg is associated with muscle atrophy (Jaitovich et al, 2015;Ceco et al, 2020), and in C2C12 muscle cell culture yields an increase in mitochondrial respiratory capacity that appears to be due to a compensatory upregulation of mitochondria (Ceco et al, 2020). Thus, whilst hypercapnia may contribute to the exacerbated muscle atrophy observed in COPD, it is possible that it may have a beneficial compensatory impact in limiting the severity of muscle mitochondrial respiratory capacity (Balnis et al, 2020b).…”
Section: Systemic Mechanisms Of Skeletal Muscle Impairment In Chronic...mentioning
confidence: 98%
“…As with studies on hypoxia, the levels of hypercapnia studied often exceed that seen in COPD patients, except perhaps under extreme conditions associated with acute exacerbations and/or in very severe patients needing lung transplant. Nonetheless, previous studies have shown that a PaCO 2 level of approximately 75 mmHg is associated with muscle atrophy (Jaitovich et al, 2015;Ceco et al, 2020), and in C2C12 muscle cell culture yields an increase in mitochondrial respiratory capacity that appears to be due to a compensatory upregulation of mitochondria (Ceco et al, 2020). Thus, whilst hypercapnia may contribute to the exacerbated muscle atrophy observed in COPD, it is possible that it may have a beneficial compensatory impact in limiting the severity of muscle mitochondrial respiratory capacity (Balnis et al, 2020b).…”
Section: Systemic Mechanisms Of Skeletal Muscle Impairment In Chronic...mentioning
confidence: 98%
“…The same research group also showed that AMPKα2 downregulated ribosomal biogenesis and thus decreased muscle protein synthesis, further negatively influencing the skeletal muscle turnover [ 106 ]. Furthermore, the regeneration of myoblasts is also impaired due to increased fatty acid oxidation caused by an enhanced rate of oxidative phosphorylation [ 8 ].…”
Section: Systemic Effects Of Hypercapniamentioning
confidence: 99%
“…The prevalence of hypercapnia is around 30–50% in patients with very severe COPD (predicted forced expiratory volume in the first second (FEV 1 ) <30%) [ 5 ]. Although hypercapnia may be beneficial to mitigate pulmonary inflammation [ 6 ], there is an increasing amount of evidence suggesting that the deleterious effects outweigh the protective ones [ 7 , 8 , 9 , 10 ]. Hypercapnia causes alveolar epithelial dysfunction, which results in alveolar oedema formation and further deterioration in gas exchange [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that carbohydrate catabolism is accompanied by the formation of large amounts of carbon dioxide, the use of fatty acids as an energy substrate contributes to less CO 2 production. Given the impaired CO 2 excretion in COPD, using fatty acids as an energy source may reduce some of the negative effects of the disease related to muscle dysfunction and shortness of breath [ 43 , 44 ]. And a diet low in carbohydrates but with the addition of medium chain triglycerides and predominantly monounsaturated fatty acids in the diet help improve pulmonary function in patients with COPD [ 45 ].…”
Section: Long-chain Fatty Acidsmentioning
confidence: 99%